Sustainable Consumer Purchasing Behavior as a Result of Kopi Kenangan's Sustainable Business Practices - Muharman, Deddy; Chair , Ahmad Achdan; Arifin , Farah Dewi (Ilomata International Journal of Social Science, 2025)
The coffee industry has become one of the sectors receiving increasing attention in the context of sustainability, both from environmental and social perspectives. As awareness grows about the importance of sustainability, consumer purchasing behavior towards coffee brands has also become a primary focus of research. This study builds upon previous research titled "Sustainable Business of Kopi Kenangan as a Startup Company in Improving the Company's Reputation and Competitiveness." This prior study, completed in 2024, concluded that sustainable business is a crucial strategy for startups to enhance reputation and competitiveness. Kopi Kenangan serves as a successful example of a startup that has integrated sustainable business practices, achieving notable success. The importance of sustainable business in boosting a startup's reputation and competitiveness is emphasized by financial and strategic benefits such as cost savings, increased productivity, improved reputation, and greater competitiveness. This study, as a continuation, explores how sustainable business is viewed from the perspective of one of the company's stakeholders: consumers. According to a 2023 Nielsen survey, 75% of respondents indicated that they are more likely to choose products from companies with clear and measurable sustainability programs, while 68% of respondents consider ESG (Environmental, Social, and Governance) factors in their purchasing decisions. The current research focuses on Kopi Kenangan, a company facing increasingly fierce competition in the coffee industry. Therefore, the question arises as to how consumer purchasing behavior towards the Kopi Kenangan brand is influenced by sustainability aspects. This study will attempt to answer whether consumers are more likely to choose brands that demonstrate a commitment to environmental and social well-being and how factors such as environmental awareness, social justice, and corporate transparency influence consumer purchasing preferences.